Balance, barycentremetry and external shape analysis in idiopathic scoliosis: What can the physician expect from it?. (August 2021) - Langlais, Tristan; Vergari, Claudio; Rougereau, Grégoire; Gajny, Laurent; Assi, Ayman; Ghanem, Ismat; Dubousset, Jean; Vialle, Raphaël; Pietton, Raphaël; Skalli, Wafa
Highlights: Balance, barycentremetry and external shape analysis in AIS are promising. Upper junctional intersegmental moment seems to distinguish the different stages of curvature. Biomarkers are relevant and need to be further investigated. Abstract: Objective: Our objective was to establish a corridor of normality for the external shape 3D parameters and then to assess these variables in adolescent idiopathic scoliosis (AIS). Methods: Adolescent with mild and severe AIS were included prospectively, as well as a control group of asymptomatic subjects. A quasi‐automatic 3D reconstruction of the spine and manual 3D reconstruction of the external envelope was performed from biplanar radiography. The center of mass position, the axial intersegmental moment resulting at the apex and junctional vertebrae, and the coronal trunk balance were automatically computed. A normality corridor of asymptomatic subjects was calculated as the range [5 th -95 th percentiles] for external shape parameters at each vertebral level. Results: Forty-one asymptomatic subjects (19 females; 22 males; 21 yo, SD=4) and sixty AIS (56 females; 4 males; 13 years old, SD=1.9; 30 mild and 30 severe; 34 thoracic curves and 26 thoraco-lumbar or lumbar curves) were included. All parameters based on the external shape showed differences between AIS and controls, as well as between mild and severe scoliosis. For instance, the intersegmental moment applied to the upper junctional vertebra was above the 95 th percentile of controls in 70% of AIS patient. The percentage of severe patients showing parameters higher than the normality corridor was significantly higher than mild patients (p<0.0001). Conclusions: The analysis of center of mass, vertebral intersegmental moment and coronal trunk balance parameters appear to be relevant in characterizing the 3D deformity of adolescent idiopathic scoliosis. The upper junctional intersegmental moment seems to be able to distinguish the different stages of curvature severity.